21 Patient-reported quality of life during golimumabinduction for moderate to severe ulcerative colitis in the united kingdom: results from the go-colitis study. (5th April 2017) - Irving, P; Sebastian, S; Probert, C; Gaya, D; Hamlin, PJ; Gillespie, G; Tate, H; Wheeler, C
Abstract : Background: GO-COLITIS (NCT02092285 ; 2013-004583-56) is a phase 4, multicentre, open-label, single-arm trial in the UK assessing efficacy of golimumab (GLM) in induction and maintenance of clinical response in patients with moderate to severe UC. We report the results of an analysis of patient-reported QoL after a 6 week induction phase Aim: Gather real-world experience of the efficacy and safety of GLM in an anti-TNF naïve cohort. Method: Anti-TNF naive patients (≥18 year) with UC ≥3 months and with moderate to severe disease were included. Patients received SC GLM on day 0 (200 mg) and day 14 (100 mg) during the 6 week induction phase, followed by GLM 50 or 100 mg 4 weekly in the 48 week maintenance phase. Clinical response and remission were summarised descriptively at the end of week 6. Patients completed the IBDQ and EQ-5D at baseline and at week 6. Results: Overall, 205 patients were enrolled (mean age, 39.3 years). Statistically significant improvements from baseline to week 6 were observed for the IBDQ total score, and the domains of bowel symptoms, emotional function, systemic symptoms, and social function. Significant improvements in the EQ-5D were observed. Conclusions: During the GLM induction phase of the GO-COLITIS study, patients with moderate to severe UC experienced significant improvements from baseline in disease-specific QoL, including bowel symptoms, emotional function, systemic symptoms, and social function. The degree of improvement in IBDQ total score exceeded the IBDQ increase cutoff (>20 points) previously identified as representative of a patient-defined improvement in an assessment of UC clinical endpoints.